Identification of feeding problems in children aged 6 Months to 7 years: adaptation and psychometrics properties of the Portuguese Version of the Pediatric Eating Assessment Tool - Brandão, Inês Guedes (2022)
Introduction: Research on feeding problems in children is limited due to lack of valid and reliable measures. Feeding problems exist across a variety of health conditions in young children.Purpose:Adapt and obtain the psychometric properties of the Portuguese adaptation of the The Pediatric Eating Assessment Tool(PediEAT); identify the main types of feeding problems in a sample of Portuguese children between 6 months and 7 years and analyze possible associated factors.Methods:The final sample consisted of 356parents, of which 278reported having achildren with no identified food problems, 63withsome type of feeding problemand 15 unsure if their children have an eating problem,aged between 6 months and 7 years. Results: Subscales demonstrated acceptable internal consistency. Total score and subscale scores were significantly different between children with and without diagnosed feeding problem. Temporal stability was adequate. Scale scores were correlated to sensory processing difficulties.Conclusion: The use of the PediEATforresearch and clinical practicein Portugalis adequatelysupported by the psychometric properties.